Dense gas scaling relations at kiloparsec scales across nearby galaxies with the ALMA ALMOND and IRAM 30 m EMPIRE surveys - Neumann, Lukas; Jiménez-Donaire, María J.; Leroy, Adam K.; Bigiel, Frank; Usero, Antonio; Sun, Jiayi; Schinnerer, Eva; Querejeta, Miguel; Krieger, Sophia K.; Bešlić, Ivana; Barnes, Ashley; Brok, Jakob den; et al. (Astronomy and astrophysics, 2025)
Dense, cold gas is the key ingredient for star formation. Over the last two decades, HCN(1 − 0) emission has been the most accessible dense gas tracer for studying external galaxies. We present new measurements that demonstrate the relationship between dense gas tracers, bulk molecular gas tracers, and star formation in the ALMA ALMOND survey, the largest sample of resolved (1-2 kpc resolution) HCN maps of galaxies in the local Universe (d < 25 Mpc). We measured HCN/CO, a line ratio sensitive to the physical density distribution, and the star formation rate to HCN ratio (SFR/HCN), a proxy for the dense gas star formation efficiency, as a function of molecular gas surface density, stellar mass surface density, and dynamical equilibrium pressure across 31 galaxies (a factor of > 3 more compared to the previously largest such study, EMPIRE). HCN/CO increases (slope of ≈0.5 and scatter of ≈0.2 dex) and SFR/HCN decreases (slope of ≈ − 0.6 and scatter of ≈0.4 dex) with increasing molecular gas surface density, stellar mass surface density, and pressure. Galaxy centres with high stellar mass surface densities show a factor of a few higher HCN/CO and lower SFR/HCN compared to the disc average, but the two environments follow the same average trend. Our results emphasise that molecular gas properties vary systematically with the galactic environment and demonstrate that the scatter in the Gao-Solomon relation (SFR/HCN) has a physical origin.